INTERNAL AND EXTERNAL FOCALIZATION IN THE NOVEL “BEAUTY AND THE BEAST” - Khoerunnisa, Vina; Juanda (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Focalization, sometimes referred to as narrative perspective or point of view, is an important component of narrative structure that affects how readers interpret a story. Focalization is an important narrative method in "Beauty and the Beast," used to illustrate certain themes, character development, and emotions. The novel’s internal focalization and other focalization strategies are examined in this qualitative research along with how they enhance the narrative as a whole. The purpose of this research is to get people’s opinions on a subject without giving much direction or guidance (Perreault and McCarthy, 2006: 176). By analyzing these strategies, we can see how they enhance the portrayal of character development, inner conflict, and underlying themes such as compassion, love, and acceptance. The results found in this study are internal, external, and emotional characteristics drawn from the 3 main characters. A greater understanding of how "Beauty and the Beast" skillfully combines several narrative motifs to tell a timeless and meaningful story of self-discovery, redemption, and the transformative power of true love is possible when one recognizes the importance of focalization in the work.